The application of human resource management functions and its role in improving the performance of youth and sports directorates. -A field study in some states in the east of Algeria- - nouri.guermat; ramdane.boukhors (sports creativity, 2025)
this study aims to identify the role of implementation of human resource management functions in improving the performance of youth and sports directorates according to the institutional performance indicators adopted in the study from the point of view of the managers of departments and offices. By using the descriptive approach, a questionnaire was designed to collect various data about the implementation of human resources management functions as well as the availability of institutional performance indicators in youth and sports directorates. After calculating validity and reliability of the questionnaire by the appropriate scientific methods, it was distributed to a class sample estimated at (80) employees in the positions of heads of offices and departments at the level of directorates. The data was collected and calculated statistically through using the SPSS program, then the results and hypotheses was analyzed and discussed in light of the theoretical background and previous studies to arrive at appropriate answers to the questions of the study. The study results showed that: - There is no statistically significant relationship between the application of human resource management functions and improving performance of youth and sports directorates according to institutional performance indicators.